PENERAPAN METODE KOPERATIF TIPE SAVI (SOMATIC AUDITORY VISUAL AND INTELLECTUAL) ANIMASI KOMPUTASI SEDERHANA UNTUK MENINGKATKAN KETUNTASAN BELAJAR KIMIA PADA MATERI IKATAN KIMIA SISWA KELAS X-6 MAN RUKOH KOTA BANDA ACEH - Djamaluddin Husita (Lantanida Journal, 2014)
Chemical bonding materials including abstract material so that learning needs to be visualized to make students more easily understand. Associated with it, has been carried out action research (PTK) with the title: Implementation Method Cooperative Type SAVI (Somatic Auditory Visual and Intellectual) Using Animation Computing Simple to Improve Learning Outcomes Chemistry in Materials Institute of Chemistry Class X-6 MAN Rukoh Banda Aceh , This study aims to determine the improvement of learning outcomes and student motivation in the concept of chemical bonding and to investigate the increasing activity of teachers and students during the learning process takes place. This classroom action research conducted in two cycles and each cycle held two meetings. In each cycle starting from planning, action, observation, assessment and reflection. The subjects were students of class X-6 MAN Rukoh Banda Aceh totaling 24 students. Results of the study in the first cycle mastery learning students 17 people (71%). While observation of teacher activity overall 71.2% (both categories) and 59.3% of student activity (enough category). In the second cycle there is an increase both student mastery learning students as well as teacher and student activity. In the second cycle mastery learning students 22 students from 24 students or 92% .. 89% of teachers activity (both categories once) and activity of students 97% (excellent category). Based on the research we concluded that using peer tutors learning model can improve learning outcomes, teacher activity and activity class X-6 MAN Rukoh Banda Aceh on chemical bonding material.